The Characteristics of Chinese Tourists in Indonesia and Its Performance in 2013−2017 - Muhammad Iqbal Rosyidi (Bina Nusantara University, 2018)
This research aimed to identify the characteristics and performance of Chinese tourists in Indonesia. To understand the characteristics of Chinese tourists, data were obtained from Passenger Exit Survey (PES) in 2016. Meanwhile, to know the performance of Chinese tourists, data were derived from monthly reports of Inbound Tourist Arrival from 2013-2017. Data and information were mostly obtained through literature studies and unstructured interviews with stakeholders and researchers at the Ministry of Tourism. This research finds several characteristics of Chinese tourists in Indonesia. Most of them are between 25-44 age group and work as professionals, managers, and employees. They like to come in groups with around seven days of stay. Moreover, they choose star hotels as the primary choice for accommodation. On average, they spend USD1.018 during their visit to Indonesia. Most of them get information about Indonesian tourism and destinations from friends/family and social media. However, the number of Chinese tourist to Indonesia has doubled in the last four years. The high penetration of the Chinese tourists takes place in Bali while the massive growth occurs in Manado.